Effect of reducing electrical stimulation rate on hearing performance of Nucleus® cochlear implant recipients. - Arora, Komal; Plant, Kerrie; Dawson, Pam; Cowan, Robert (International Journal of Audiology, 2025)
Objective: To evaluate whether a 500 pulses per second per channel (pps/ch) rate would provide non-inferior hearing performance compared to the 900 pps/ch rate in the Advanced Combination Encoder (ACE™) sound coding strategy. Design: A repeated measures single-subject design was employed, wherein each subject served as their own control. All except one subject used 900 pps/ch at enrolment. After three weeks of using the alternative rate program, both programs were loaded into the sound processor for two more weeks of take-home use. Subjective performance, preference, words in quiet, sentences in babble, music quality, and fundamental frequency (F0) discrimination were assessed using a balanced design. Study sample: Data from 18 subjects were analysed, with complete datasets available for 17 subjects. Results: Non-inferior performance on all clinical measures was shown for the lower rate program. Subjects' preference ratings were comparable for the programs, with 53% reporting no difference overall. When a preference was expressed, the 900 pps/ch condition was preferred more often. Conclusion: Reducing the stimulation rate from 900 pps/ch to 500 pps/ch did not compromise the hearing outcomes evaluated in this study. A lower pulse rate in future cochlear implants could reduce power consumption, allowing for smaller batteries and processors.